The Great Wall and Eggs: A Hong Kongers’ Political-Spiritual Movement in the Post-National Security Law Era - Kung, L.Y. (University of jaffna, 2024)
Receiving the Jerusalem prize for the Freedom of the Individual in Society in 2009, Haruki Murakami used the egg-versus-wall metaphor in his address, “Between a high, solid wall and an egg that breaks against it, I will always stand on the side of the egg.” This metaphor became a symbol widely used among Hong Kong protestors in the 2010s. It not only recommended where Hong Kongers should stand, but also motivated them to confront the system courageously. Since the implementation of the national security law in Hong Kong in June 2020, open protest has rarely occurred in the city. The government considers the law as an effective means to restore Hong Kong “from chaos to order, from stability to prosperity”, but Hong Kongers have a different interpretation. The principle of “one country, two systems” has been weakened because the emphasis on the “one country” has become more prominent. In order to counter the hegemony of the system represented by the Great Wall, those who choose to stay in Hong Kong have initiated a new political-spiritual movement characterized by transitioning from organizing mass social movement to Wei Lu , which means gathering together and supporting one another, shifting their focus from the external environment to Chu Xin , protecting their original impetus, developing a lifestyle politics. This political-spiritual movement goes beyond the traditional forms of political activism and incorporates elements of friendship, personal transformation, and collective consciousness. This article aims to reflect on the nature of the Great Wall in terms of ontological security, the lived experiences of Hong Kongers as fragile eggs and the political-spiritual movement of Hong Kongers from a theological perspective.
Keywords: Political-spiritual Movement; “Great wall”; “Eggs”; Lived experiences of hong kongers